The effect of ocular dominance on decision making in a virtual environment - Suk, Hae Jung; Kim, S. J. (Advances in Intelligent Systems and Computing, 2020)
Human laterality is the preference of an individual to use one side of their body rather than the other. Ocular dominance, also known as eye dominance, is one type of laterality in that eye dominance affects human visual perception. This study explores how ocular human laterality is associated with decision making in determining one choice from the left or right and top or bottom. Two simple tasks are developed running in a virtual environment in which a user wears a head-mounted display and observes two 3D ball shape objects that one moves to the left and the other moves to the right side of their eyes. The user performs the same task as the direction of the ball movement is changed to up and down. An eye-tracking device is used to measure the users’ decision on the two tasks by tracking down their eye movements. A user study conducted with a total of 20 college students, ages ranged from 18 to 30 years old, revealed that there was a significant relationship between eye dominance and their decision making.
Keywords: College students; Eye dominance; Eye tracking devices; Head mounted displays; Human laterality; Human visual perception; Ocular dominance; Running-in; Eye dominance; Eye-tracking; Head-mounted display; Human laterality; Ocular dominance; Virtual environments; Visual perception